1999
DOI: 10.1038/sj.hdy.6885820
|View full text |Cite
|
Sign up to set email alerts
|

Contact zones between chromosomal races of Mus musculus domesticus. 1. Temporal analysis of a hybrid zone between the CD chromosomal race (2n=22) and populations with the standard karyotype

Abstract: A temporal analysis of a hybrid zone between chromosomal races of Mus musculus domesticus was performed to evaluate its dynamics over a 20-year period. The transect chosen was one previously analysed by Spirito et al. (1980) across the hybrid zone between the chromosomal race CD 2n 22 (central Italy) and the surrounding populations with standard karyotype (2n 40). The results show that 20 years of hybridization have not had any signi®cant e ect on the position of this hybrid zone, nor on the location of its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 27 publications
4
39
0
7
Order By: Relevance
“…These results suggest that processes of introgression of animals, carrying diverse chromosomal combinations, towards the centre of polymorphism may alter the expected metacentric frequencies in the area. The arrival of allochthonous mice in the centre of a metacentric zone has also been reported in Rb populations from Italy (Franchini et al, 2007;Castiglia and Capanna, 1999) and Madeira (Nunes et al, 2005). In those cases, as may also occur in the Rb zone of Barcelona, the action of humans on the natural landscape has influenced the dynamics of commensal mice (Chatti et al, 1999;Castiglia and Capanna, 1999).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…These results suggest that processes of introgression of animals, carrying diverse chromosomal combinations, towards the centre of polymorphism may alter the expected metacentric frequencies in the area. The arrival of allochthonous mice in the centre of a metacentric zone has also been reported in Rb populations from Italy (Franchini et al, 2007;Castiglia and Capanna, 1999) and Madeira (Nunes et al, 2005). In those cases, as may also occur in the Rb zone of Barcelona, the action of humans on the natural landscape has influenced the dynamics of commensal mice (Chatti et al, 1999;Castiglia and Capanna, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…The arrival of allochthonous mice in the centre of a metacentric zone has also been reported in Rb populations from Italy (Franchini et al, 2007;Castiglia and Capanna, 1999) and Madeira (Nunes et al, 2005). In those cases, as may also occur in the Rb zone of Barcelona, the action of humans on the natural landscape has influenced the dynamics of commensal mice (Chatti et al, 1999;Castiglia and Capanna, 1999). Passive transport via vehicles, especially in farming areas, may have promoted introgression events independently of the common mouse dispersion (Cucchi et al, 2005;Franchini et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, the absence of genetic differentiation can be interpreted as the presence of free gene flow between races or it could be due to the recent formation of the races (Britton-Davidian et al, 1989). Many studies have focused on the contact zones between Robertsonian races and the standard one (see Searle, 1993 for a review; Castiglia and Capanna, 1999a;Gundü z et al, 2001a). All these studies have found hybrids showing trivalents at diakinesis, with hybrid zone widths from 0.5 km (Chatti et al, 1999) to 30 km .…”
Section: Introductionmentioning
confidence: 99%